The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.memsci.2018.10.072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quantification of structure and flow in multichannel polymer membranes by MRI

Abstract: Polymeric multichannel hollow fiber membranes were developed to reduce fiber breakage and to increase the volume-to-membrane-surface ratio and consequently the efficiency of filtration processes. These membranes are commonly used in ultrafiltration and are operated in in-out dead-end mode. However, some of the filtration details are unknown. The filtration efficiency and flow in the multichannel membranes depend on filtration time and are expected to vary along spatial coordinates. In the current work, in-situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
(14 reference statements)
4
23
0
3
Order By: Relevance
“…The axial velocity magnitude at the shell side is highest at the maximum distance between the membrane and inner tube wall, caused by small local pressure differences on the lumen side [33]. This is in good agreement with the CFD results shown in Figure 3 and Figure 4.…”
Section: Mri Velocimetry -Dead-end Pure Water Forward Permeationsupporting
confidence: 90%
See 1 more Smart Citation
“…The axial velocity magnitude at the shell side is highest at the maximum distance between the membrane and inner tube wall, caused by small local pressure differences on the lumen side [33]. This is in good agreement with the CFD results shown in Figure 3 and Figure 4.…”
Section: Mri Velocimetry -Dead-end Pure Water Forward Permeationsupporting
confidence: 90%
“…Recently, Schuhmann et al used MRI to investigate the filtration behavior in multibore membranes [33]. The authors hypothesize that the location of the membrane in the module might influence the velocity field.…”
Section: Introductionmentioning
confidence: 99%
“…The MIONs with a mean diameter of 100 nm are composed of iron oxide clusters embedded in a matrix of dextran and are coated with casein proteins to be chemically compatible with the feed. In previous studies [21][22][23][24][25]27,28], it was shown that the contrast agent is embedded in the deposit layer and does not diffuse back into the feed solution separately from the deposit nor significantly permeates the membrane. To confirm and investigate the behaviour of these MIONs, the deposit layer was taken out of the hollow fibre membrane after filtration with MIONs and put into a glass tube filled with skim milk, also including the contrast agent.…”
Section: Mri Contrast Agentmentioning
confidence: 99%
“…Viscosities of water and permeate were measured with an Anton Paar MCR 302 rheometer (Anton Paar, Graz, Austria) using the double-gap geometry. The rehydrated skim milk powder is referred to as skim milk hereafter [23].…”
Section: Reconstituted Skim Milk Solutionmentioning
confidence: 99%
See 1 more Smart Citation